The Effect of Leadership Style and Internal Communication on Employee Work Effectiveness at the Ministry of Public Works and People's Housing Directorate General of Bina Marga Bandar Lampung - Suroyo Suroyo (Peneliti.net, 2022)
This study aims to determine whether there is an influence of leadership style and internal communication on the work effectiveness of employees at the Ministry of Public Works and Public Housing at the Directorate General of Bina Marga, Bandar Lampung. This research is a quantitative research. The population in this study were all employees of the Office of the Ministry of Public Works and Public Housing, Directorate General of Bina Marga Bandar Lampung, which did not include employees who held the position of a Head of Service and 5 Heads of Sections, so that the population in this study was 90 employees. Testing the hypothesis in this study using multiple regression analysis. Based on the descriptive analysis, the percentage obtained by the leadership style is 84.24% and is included in the very good category, the level of internal communication is 86%, including the very good category, while the work effectiveness level is 78.78%, including the good category. Meanwhile, based on the calculation of multiple linear regression analysis obtained the equation: Y = 8,730 + 0,405 X1 + 0,513 X2. Based on the calculation of multiple linear regression analysis also obtained F-count of 17,234 with a significance of 0.000.